Effects of Sex, Age, and Body Size on Flight Performance of Monochamus alternatus (Coleoptera: Cerambycidae), a Vector of Pine Wood Nematodes, Using Flight Mills - Jong-Kook Jung; Chayoung Lee; Beomjun Jang; Youngwoo Nam (Insects)
To understand the spread of the pine wood nematode Bursaphelenchus xylophilus (Steiner and Buhrer, 1934; Nickle, 1970) and identify infected trees, the dispersal ability of insects was examined. In this study, the effects of sex, adult age, and morphological traits on the flight performance (such as flight distance, time, and speed) of Monochamus alternatus (Hope, 1843) were investigated using flight mills. Over a period of 8 weeks, a total of 42 newly emerged adult beetles were tethered to flight mills once a week. Flight distance and time were recorded for 2 h during each session. The total flight distance of individuals that flew more than 100 m during each session was calculated. The results showed that females flew an average of 6.65 km, for 59.6 min, while males flew an average of 9.89 km, for 85.8 min. In a single flight experimental session, both sexes could fly up to approximately 2 km and were found to fly at an average speed of 1.9 m s−1. In our principal component analysis (PCA), the first and second principal components were found to be highly correlated with the sex, morphological traits, and flight performances of M. alternatus. This study demonstrates that the flight ability of M. alternatus varies significantly according to body size and sex, which is fundamental and crucial for understanding the dispersal patterns of pine wilt disease.